NILAI-NILAI YANG TERKANDUNG DALAM TARIAN ZAPIN DAN UPAYA PELESTARIANNYA DI DESA MESKOM BENGKALIS RIAU - Jailani, Ahmad; Dora, Esya; Azizah, Kurniawati (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research was conducted in the village of Meskom. The purpose of this study is to identify the values contained in zapin dance and its preservation efforts in Meskom village. This research is a field study conducted in Zapin village, Meskom village, Bengkalis Regency. The subjects of this study were zapin traditional figures in zapin village, bengkalis regency, and the values contained in zapin dance and its preservation efforts in meskom village, Bengkalis regency were the subject of this study. In this study, the author assumes the population consists of 1 studio leader. The goal is to preserve zapin dance during kut and cultural festivals. Last year, other countries also came to this training ground. He came with a specific purpose: He wanted to learn Zapin's dance. These people introduced us to their culture and we reintroduced our culture.